Increasing drought frequency in the central Zagros Mountains of western Iran over the past two centuries - Beiranvand, Samira; Bayramzadeh, Vilma; Attarod, Pedram; Pourtahmasi, Kambiz; G. Pypker, Thomas; Bräuning, Achim; Nadi, Mahdi (Journal of Arid Environments, 2024)
The Zagros region in western Iran has experienced prolonged drought, significantly impacting water resource and forest ecosystems over the past few centuries. Understanding historical prolonged drought is crucial for making precise forecasts of shifts in regional drought in the Zagros region. Due to the lack of comprehensive historical records, the use of proxy records is considered a valuable tool for reconstructing past drought variations. We aimed to construct a tree-ring chronology of Juniper (Juniperus polycarpus) in the central Zagros region to comprehend its growth response to climate variables. We cored 25 J. polycarpus trees from the Keygooran forest reserve in western Iran and developed the tree ring chronology (1802–2022) using dplR. The relationships between tree growth and climate variables of monthly mean temperature, precipitation, PDSI (Palmer Drought Severity Index), and SPEI (Standardized Precipitation Evapotranspiration Index) were examined. The analysis revealed a strong positive correlation between tree growth and SPEI March-September of 1990–2018 on a 48-month timescale with a 2-year lag (r = 0.61, p < 0.05) which was included in the transfer model. Consequently, the SPEI-48 March-September was reconstructed for the period 1802–2022. On this reconstruction, several extremely dry years in 1832, 1867, and 1876 and extremely wet years in 1807, 1814, 1838, 1850, 1907, and 1908 years were identified, some of them aligning with historical records in Iran. Furthermore, there was a relationship between SPEI-48 March-September and teleconnection events suggesting that certain drought occurrences in the area were associated with the El Niño-Southern Oscillation (ENSO). Consequently, this reconstruction can serve as a reliable proxy for large-scale drought variability in the Zagros region of western Iran. Moreover, our research underscores the utility of SPEI in reconstructing the history of semi-arid climate conditions.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Chronology; Drought reconstruction; Extreme drought; Tree-rings